Arquitectura franciscana. La evangelización en el occidente de la tierra caliente de Michoacán, énfasis siglos XVI-XVII - Valle González, Teresita (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
New Spain convent architecture has been the basis of numerous studies, without doubt these works, material expression of the project of evangelization and Acculturation initially undertook the Franciscans, Dominicans and Augustinians in New Spain show the new spatial order by which He intended to carry out the cultural change of Indian society. In Michoacan, both Franciscans (1525) and Augustinians (1535) undertook the work evangelization and indigenous acculturation since the mid-sixteenth century. Activity the Franciscans remained almost until the late eighteenth century, culminating in the secularization of its doctrines. Initially the Franciscans remained in the central part of the ancient bishopric of Michoacan, and late in the sixteenth century start extend its work to the north and south, leaving behind examples of their material work. Our study focuses on the southern part of the ancient bishopric, specifically in the West of the Tierra Caliente of Michoacán to the Franciscans penetrated taking as door Tancítaro settlement. The work material and spiritual these friars in the Tierra Caliente of Michoacán has been little studied, and although the Most of this material work has disappeared still remain some architectural remains that speak about the passage of evangelization in this area. Intending to delve to study a little convent architecture analyzed and which is also part of the history of architecture of Michoacan, is She decided to address in this investigation the case of the doctrine of Tancítaro, founded mid-sixteenth century and located - at the time - in the west of the old Bishopric of Michoacan.

La arquitectura conventual novohispana ha sido la base de numerosos estudios, sin duda alguna estas obras, expresión material del proyecto de evangelización y aculturación que emprendieron inicialmente los franciscanos, dominicos y agustinos en la Nueva España muestran el nuevo orden espacial mediante el cual se pretendía llevar a cabo el cambio cultural de la sociedad indígena. En Michoacán, tanto franciscanos (1525) como agustinos (1535) emprendieron la labor de evangelización y aculturación indígena desde mediados del siglo XVI. La actividad de los franciscanos permaneció casi hasta finales del siglo XVIII culminando con la secularización de sus doctrinas. Inicialmente los franciscanos permanecieron en la parte central del antiguo obispado de Michoacán, ya avanzado el siglo XVI empiezan a extender su labor hacia el norte y el sur dejando a su paso ejemplos de su obra material. Nuestro estudio se centra en la parte sur del antiguo obispado, específicamente en el occidente de la Tierra Caliente de Michoacán a la que los franciscanos se adentraron tomando como puerta el asentamiento de Tancítaro. La obra material y espiritual de estos frailes en la Tierra Caliente de Michoacán ha sido poco estudiada, y aunque la mayor parte de esta obra material ya ha desaparecido aún permanecen algunos vestigios arquitectónicos que hablan sobre el paso de la evangelización en esta zona. Con la intención de adentrarnos al estudio de una arquitectura conventual poco analizada y que también forma parte de la historia de la arquitectura de Michoacán, se decidió abordar en esta investigación el caso de la doctrina de Tancítaro, fundada a mediados del siglo XVI y ubicada – en su momento – en el occidente del antiguo Obispado de Michoacán.
Facultad de Arquitectura. Maestría en Arquitectura, Investigación y Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-M-2007-0005; Arquitectura franciscana; Evangelización; Conventual; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1551